Thirty-Seventh Meeting of the National Development Council 12th and 13th July, 1984 Summary Record - Planning Commission (Planning Commission, 1984)
Welcoming the Members to the meeting of the National Development Council, Shri S. B. Chavan, Minister of Planning , stated that the work relating to the formulation of the Approach to the Seventh Five year Plan was started in June 1983, with the exercises carried out for the Mid-term Appraisal of the Sixth Plan 1980-85 providing the base for it.
Government of India, Planning Commission